Reassessing Nepotism: Wederrechtelijk and Onrechtmatige Daad in Indonesian Law - Murtadho, Nazhif Ali; Warjiyati, Sri (Corruptio, 2024)
This research examines nepotism as a form of Corruption, Collusion, and Nepotism (KKN), which has significantly undermined social and institutional order in Indonesia. The problem stems from the negative impacts of KKN on community welfare, resource misuse, and the erosion of public integrity and morals. The main goal of the paper is to analyze nepotism from a positive legal perspective by exploring the conceptual differences between "onrechtmatige daad" in civil law and "wederrechtelijk" in criminal law. The study uses a doctrinal approach that integrates conceptual, statutory, and case analysis, focusing on Law Number 28 of 1999 and Constitutional Court Decision Number 90/PUU-XXI/2023 as key case studies. Through evaluative, argumentative, and prescriptive techniques, the research develops arguments concerning the classification of nepotism as either a criminal or civil matter. The findings highlight that while both legal concepts—onrechtmatige daad and wederrechtelijk—serve to protect individual rights and public interests, they are applied differently. The study concludes that nepotism, which has caused systemic harm to fair and transparent governance, should be classified as a criminal act (wederrechtelijk) to ensure legal certainty and maximize the repressive effects of the law, adhering to the principles of lex scripta, lex certa, and lex stricta. As a recommendation, the government and the DPR should revise Law Number 28 of 1999 to strengthen the norms regarding nepotism and submit a material review to the Constitutional Court to align the law with the principle of legality, ensuring optimal protection of the public interest.